SCE513 : Science laboratory safety / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
Laboratory investigations are essential for the effective teaching and learning of science. A school laboratory investigations an experience in the laboratory, classroom, or the field that provides students with opportunities to interact directly with natural phenomena or with data collected by others using tools,materials, data collection techniques, and models Inherent in laboratory-based activities is the potential for injury. As professionals, teachers of science have a duty of care to ensure the safety of students, teachers, and staff. Duty of care is defined as an obligation, recognized by law, requiring conformance to a certain standard of conduct to protect others against unreasonable risk As such, science educators must act as a reasonably prudent person would in providing and maintaining a safeLearning environment for their students. This course will expose science teachers with safety and health knowledge and management to be applied at school laboratories. Safety and the minimisation of risk (not avoidance of risk) is of central importance in science and science education - and this is the reason that laboratories, specialised equipment and appropriate procedures need to be used and skills developed. Topics include fundamental of OSH management for science teachers , safe handling of biological, chemical, fire, electrical and radiotion safety.. Focuses on safety regulations and recommendations, and proper materials handling in school laboratories which also covers the laboratory risk assessment, medical surveillance requirements as part of an occupational health program, routine safety surveillance activities, identification of appropriate decontamination methods for biological, radiological, chemical , elctrical and fire accidents, spills, first aid requirement, accidents . injury and insurance in laboratories